β-Hydroxybutyric Inhibits Vascular Calcification via Autophagy Enhancement in Models Induced by High Phosphate - Liang, Jianwen; Huang, Jieping; He, Wanbing; Shi, Guangzi; Chen, Jie; Huang, Hui (Frontiers in Cardiovascular Medicine, 2021)
Background: Vascular calcification (VC) is a landmark of aging, while β-hydroxybutyric acid (BHB) induced by calorie restriction has been identified as a promising factor to extend the lifespan. However, the effect of BHB on VC and the potential mechanism remain unknown. Methods: A total of 160 subjects with or without metabolic abnormalities (MAs) were assigned to four groups according to different calcification severities. The association between BHB, MAs, and VC was investigated via mediation analysis. Then, with high phosphate-induced calcification models, the effect of BHB on arterial ring calcification and osteogenic phenotypic differentiation of vascular smooth muscle cells (VSMCs) was investigated. Hereafter the expressions of autophagy biomarkers, autophagy flux, and effects of autophagy inhibitors on VC were detected. Results: Severe VC was observed in the elderly, accompanied with a higher proportion of hypertension, chronic kidney disease, and lower estimated glomerular filtration rate. The serum BHB level was an independent influencing factor of VC severities. With mediation analysis, BHB was determined as a significant mediator in the effects of MAs on VC, and the indirect effect of BHB accounted for 23% of the total effect. Furthermore, BHB directly inhibited arterial ring calcification and osteogenic phenotypic differentiation in VSMCs, accompanied with autophagy enhancement in VSMCs. In accordance, the inhibition of autophagy counteracted the protective effect of BHB on VC. Conclusion: The present study demonstrated that BHB mediated the effects of MAs on VC; then, it further elucidated that BHB could inhibit arterial and VSMC calcification via autophagy enhancement.